The neglected dimension of well-being: Analyzing the development of "conversion efficiency" in Great Britain - Martin Bindera; Tom Broekel (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
In Amartya Sen's capability approach, policy makers can focus on different levels to influence the well-being of a society. We argue that improving capability to function as well as absolute levels of functioning achievement should be complemented by attention given to improving individuals' conversion efficency, i.e. the efficiency with which individual resources are converted into well-being. In order to examine effects of policies on conversion efficiency and to better understand the trajectories of human well-being over time, it is necessary to measure the development of conversion efficiency. We suggest an intertemporal index of conversion efficiency estimated via a nonparametric order-m approach borrowed from the production efficiency literature to analyze this development of our welfare measure. We exemplify this approach using micro level data from the British Household Panel Survey (BHPS), tracking conversion efficiency for a set of basic functionings in Great Britain from 1991 to 2006. We find that under 30% of the British populace were efficient in their conversion of resources into functionings during the sample horizon. Moreover, age, education and self-employment increase an individual's conversion efficiency, while living in London, being disabled and being separated, divorced or widowed all decrease conversion efficiency. Being married also decreases the conversion efficiency and we find few evidence of gender disparities in conversion efficiency.
Keywords: I12; I31; D60; 330; capability approach; conversion efficiency; efficiency analysis; intertemporal development; Capability Approach; Lebensqualität; Zeitpräferenz; Technische Effizienz; Schätzung; Großbritannien